How to Start the Path of Innovation? - Suárez Mella, Rogelio (2013)
This article presents the theoretical fundamentals of the innovating process in current companies, whose main objective is to analyze conceptually the term innovation, which has not always been very well used by some entrepreneurs and scholars. To do it, it has been necessary to treat some aspects concerning knowledge management, science, technics, technology, transfer, innovation, prospective, innovation management functions, and other important considerations related to these concepts within the scientific and business world as well. Furthermore, another essential element in this publication is the strategic focus of Innovation Management carried out by leader global companies and the criteria of some international ñgures regarding the subject matter together with their view on the emphasis of the economic, social and environmental impact. As a result of the analysis, it has been possible to establish some indicators in order to build up innovation culture within the company. By the same token, some final considerations to strengthen the statement innovate or perish are also presented in this study.